Influence of indicators of successful combat for the ball on the performance of matches in the Russian Premier Football League - Suetin, P. S.; Zakharova, A. V.; Naboychenko, E. S. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the relationship between teams` performance in successful martial arts and the results of matches in the Russian Premier Football League (RPL).